ANALYSIS OF STAKEHOLDER’S BEHAVIOR TOWARDS MANAGEMENT OF COMMUNITY FOREST IN WEST BOGOR AREA, INDONESIA - Hero, Yulius; Ikhsan, Mahtuf (PEOPLE: International Journal of Social Sciences, 2017)
Community forest ha played an important role in supplying the needs of rural timber in JavaIsland, Indonesia since a long time ago. This forest produces % of the community's wood demand for the island. West Bogor is a potential area of community forest development in Bogor Regency. The development of community forest enterprises is also followed by the development of various stakeholders on the management of this forest with various forms of behavior and their respective interests. The objectives of the research are analysing involved stakeholders and their roles and also analysing the behavior of involved stakeholders with their interest and power. The method used in this research is based on institutional approach that using Situation-Structure-Behavior-Performance approach. Research result shows there are 17 stakeholders who are related to the development of community forest in West Bogor area. The behavior analysis suggests that most of the farmers who own community forest (outside the farmers group) agreed (Perception) and will realize actions/ agreed (Action) on the development of community forest in the farmer groups. Stakeholder key players include owner farmers, tenant farmers (land owned by external villages), local traders and rental industry. Whereas context setters are local government. Behavioral analysis also shows that the Rimba Lestari farmer group in Leuwiliang District is preferred by the surrounding community outside this group compared to the Barokah farmer group-Rumpin sub-district. From the research results, it is expected to become the policy recommendation for the government towards the development of community forest enterprises in Bogor regency.